SURG-10. PERMANENT CARRIER-EMBEDDED CESIUM-131 BRACHYTHERAPY FOR THE SALVAGE TREATMENT OF PREVIOUSLY IRRADIATED, RECURRENT BRAIN METASTASES. (14th November 2022) - Imber, Brandon; Beal, Kathryn; Reiner, Anne; Giantini-Larsen, Alexandra; Yang, Jonathan; Aramburu-Nunez, David; Cohen, Gil'ad; Brennan, Cameron; Tabar, Viviane; Young, Robert; Moss, Nelson
Abstract: BACKGROUND: Salvage of recurrent, previously-irradiated brain metastases (rBrM) is a significant clinical challenge. High local failure is seen following salvage resection without adjuvant re-irradiation, while re-irradiation is associated with high radionecrosis rates. Salvage surgery plus intraoperative Cs131 brachytherapy may offer dosimetric and biologic advantages including improved local control versus observation, with reduced integral brain dose versus re-irradiation. METHODS: A prospective registry of consecutively treated patients with post-stereotactic radiosurgery (SRS) rBrM was analyzed. Following resection, cavities were implanted with commercially-available, collagen-matrix embedded Cs131 seeds (GammaTile, GT Medical Technologies) prescribed to 60Gy at 5mm from the cavity. RESULTS: Twenty patients underwent 24 operations with Cs131 implantation in 25 cavities. Previous SRS occurred a median of 358d preoperatively (range=56-1334). Median maximum preoperative diameter was 3.0cm (range=1.1-6.3) and enhancing volume was 9.5cm 3 (range=0.6-69.7). Gross- or near-total resection was achieved in 60%. A median of 16 Cs131 seeds (range=6-30), with a median activity of 3.5U/seed were implanted. Maximal preoperative diameter and enhancing volume were weakly associated with the number of implanted seeds (correlation coefficients=0.50, 0.41, respectively). There was one postoperative wound dehiscence in a multiply resected and irradiated patient with hydrocephalus. With median follow-up of 1.6 years for survivors, 2 tumors recurred (one in-field, one marginal) resulting in 9.8% 1-year progression incidence (95%CI=0.0-23.2). Radiographic seed migration was identified in 7/25 cavities (28%) on scans ranging from 1.9-11.7 months post-implantation, without clinical sequelae. CONCLUSIONS: With >1 year of follow-up, intraoperative brachytherapy with Cs131 implants was associated with a high rate of local control and a favorable toxicity profile. Modest correlation between preoperative tumor geometry and implanted tiles with high associated cost suggests a need to optimize planning criteria. A randomized trial of salvage resection with or without Cs131 is ongoing (NCT04690348) to assess the incremental benefit of brachytherapy.